2009
DOI: 10.1021/es803534f
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Organic Aerosol-Forming Reactions of Glyoxal with Amino Acids

Abstract: Glyoxal, the simplest and most abundant alpha-dicarbonyl compound in the atmosphere, is scavenged by clouds and aerosol, where it reacts with nucleophiles to form low-volatility products. Here we examine the reactions of glyoxal with five amino acids common in clouds. When glyoxal and glycine, serine, aspartic acid or ornithine are present at concentrations as low as 30/microM in evaporating aqueous droplets or bulk solutions, 1,3-disubstituted imidazoles are formed in irreversible second-order reactions detec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
281
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 237 publications
(315 citation statements)
references
References 44 publications
(65 reference statements)
21
281
1
Order By: Relevance
“…[6,34] They might also form during cloud and fog droplet evaporation, where GLY may be present in its monohydrated form. [58] Detection of tartarate during the GLY þ OH experiments herein provides key verification of the organic radical-radical oligomer formation mechanism proposed by Lim et al [21] This chemistry is detectable in experiments with 1 mM of organic, and is predicted to be dominant at the high (1-10 M) concentrations of organics found in wet aerosols. Thus, oxalate is the major product of dilute (in cloud) GLY oxidation and oligomers [21] and organic nitrogen [34] are major products of GLY chemistry in wet aerosols.…”
Section: Atmospheric Implicationssupporting
confidence: 77%
See 1 more Smart Citation
“…[6,34] They might also form during cloud and fog droplet evaporation, where GLY may be present in its monohydrated form. [58] Detection of tartarate during the GLY þ OH experiments herein provides key verification of the organic radical-radical oligomer formation mechanism proposed by Lim et al [21] This chemistry is detectable in experiments with 1 mM of organic, and is predicted to be dominant at the high (1-10 M) concentrations of organics found in wet aerosols. Thus, oxalate is the major product of dilute (in cloud) GLY oxidation and oligomers [21] and organic nitrogen [34] are major products of GLY chemistry in wet aerosols.…”
Section: Atmospheric Implicationssupporting
confidence: 77%
“…3a reaction is more likely to occur during droplet evaporation or in wet acidic aerosols. [58] The nitration of hydrated GLY (diols) with HNO 3 (Fig. 3b) is also more likely to occur in very concentrated solutions, as might be present in evaporating droplets and in wet aerosols.…”
Section: Organic Nitrogenmentioning
confidence: 99%
“…Formic acid, especially under acidic conditions, is a sufficiently strong reducing agent to complete the reductive amination step as shown in Scheme 1. Formic acid was not 30 detected in this study in either positive or negative ion mode (as m/z 47 or 45, respectively) but it has been reported as a side product of glyoxal/AS and methyglyoxal/AS in several other studies (Galloway et al, 2009;De Haan et al, 2009;Sareen et al, 2010;Yu et al, 2011). The evidence outlined here lends confidence to our assignment of m/z 109 as 2,5-DMP.…”
Section: Pyrazine-based Chromophoressupporting
confidence: 78%
“…Aqueous phase reactions, in contrast, appear to form larger and highly functionalized chromophores that often include reduced nitrogen species (Baduel et al, 2010;Duarte et al, 2004). This material can be formed in Maillard-type reactions between small carbonyl compounds and ammonia or amines, which have been shown to produce 15 oligomeric species and BrC chromophores (termed aqueous brown carbon or aqBrC); a few representative studies include De Haan et al (2011), Kampf et al (2012), Nguyen et al (2012), Laskin et al (2014), andLin et al (2015). Even simple aqueous mixtures of one dicarbonyl (glyoxal or methylglyoxal) and ammonia or a small amine produces myriad products and, under most conditions, yellow to brown color.…”
Section: Introductionmentioning
confidence: 99%
“…They can also undergo photooxidation and oxidation reactions with OH radicals, NO 3 radicals and O 3 in the ambient atmosphere to form non-volatile aerosol components. [13,[18][19][20] De Haan et al [21,22] observed that reactions between glyoxal and amines or amino acids can produce light-absorbing, nitrogen-containing imidazoles and oligomers. Particle phase amines have been extensively observed in many areas [9,17,[23][24][25] especially in ultrafine particles during nucleation [26][27][28] and particle growth [29] events.…”
Section: Introductionmentioning
confidence: 99%